ARABIC TEACHING METHODS IN BORNEO: A CASE STUDY OF MUHAMMADIYAH NURSING COLLEGE SAMARINDA – EAST KALIMANTAN – INDONESIA - Yani, Dr. Achmad (IJRDO- Journal of Educational Research, 2017)
This study was aimed to identify the feasibility of Arabic teaching methods in Borneo by acase study of Muhammadiyah Nursing College of Samarinda – East Kalimantan– Indonesia.The Communicative Language Teaching (CLT) were used as benchmarks to evaluate theArabic teaching methods in the college. This is a qualitative study where the researchercollected data by interviewing an Arabic expert who is teaching Arabic course in the collegeabove. The research result found that Arabic lesson in Muhammadiyah Nursing College ofSamarinda – East Kalimantan– Indonesia used selective teaching method, it is meaning thelecturer decided which method suited students’ situation and needs and wasn’t bound to anyparticular method. However, in terms of percentage, translation method was the mostdominant. The students were trained to master all language skills (listening, speaking,reading and writing) when they studied Arabic, however reading and writing skills dominatedother skills. The language of instruction in teaching Arabic is Indonesian Language.Excessive usage of translation and the usage of Indonesian Language as the language ofinstruction could affect student’s skill in communicating in Arabic.